Kesesuaian Peresepan Obat Rawat Jalan BPJS Kesehatan dengan Formularium Nasional di Rumah Sakit Bekasi - Rangka, Febbyasi Megawaty; Susilo, Ayu Purnama Sari; Sugiarti, Yohana Inge; Purnamasari, Alfonsia (Pengurus Pusat Ikatan Apoteker Indonesia, 2024)
Prescriptions for patients of the Health Social Security Organizing Agency (BPJS) in hospitals in accordance with the National Formulary (FORNAS) guidelines regulate drugs that must be given to patients according to complaints. The benefits of FORNAS optimize the quality of pharmaceutical services, especially to BPJS Kesehatan social security patients. Hospital X Bekasi is a type C private hospital located in Bekasi, West Java as an Advanced Referral Health Facility (FKRTL) prescribing services for chronic diseases with outpatient polyclinic services with a 30-day limit according to restriction requirements or indications Many prescriptions are not in accordance with FORNAS and drugs that have not been registered in FORNAS so that their administration is based on the policies of the Medical Committee and the hospital director at the expense of the hospital. The aim of the study was to determine the percentage of prescribing conformity that was not in accordance with FORNAS at Hospital X Bekasi from January to March 2021. Non-experimental research method with a descriptive approach conducted retrospectively on a population of 6,891 specialist polyclinic outpatient prescription sheets from January to March 2021. The number of samples based on the calculation of the slovin formula is 400 prescription sheets. Inclusion criteria were outpatient specialist polyclinic prescriptions with BPJS Health coverage and exclusion criteria were outpatient prescription sheets for non-chronic diseases. The suitability of drug prescription to FORNAS at X Bekasi Hospital was 84,5 % of the total prescriptions. Prescription concordance in specialist clinics was highest at 100% cardiac clinic, 97.5% urology clinic, 95% pulmonary clinic, 91.25% internal medicine clinic and lowest at 38.75% neurology clinic.. The most common drug found not in accordance with FORNAS was Mecobalamin 500 mg in urology polyclinic 100%, internal medicine polyclinic 42.86%, neurology polyclinic 28.57% and lung polyclinic 25%. The mismatch of prescription writing based on FORNAS causes an inefficient reduction in INA-CBGs costs affecting long LOS and increasing the total real cost of patients. Suggestions need to socialize to doctors to write prescriptions in accordance with FORNAS and conduct periodic evaluations of prescribing discrepancies